Antioxidant and Toxicity Assay-guided Isolation of Herniarin from Equisetum debile Roxb. (Equisetaceae) - Ang, Aileen May Gabule; Peteros, Nonita Picardal; Uy, Mylene Mondarte (Asian Journal of Biological and Life Sciences, 2019)
Introduction:Bioassay-guided isolation of the bioactive components fromEquisetum debileRoxb. (“sumbak”) was conducted.Objectives:This study aimed to isolate and characterize bioactive components fromE. debile.Materials and Methods:Ethanolic extract of whole plant sample ofE. debilewas sequentially partitioned to obtain the bioactive choroform-soluble (EdC) partition. EdC was purified via chromatographic techniques. Fractions obtained after purification were analyzed for cytotoxic and antioxidant properties. Brine shrimp lethality as well as in vitro antioxidant assays such as 2,2-diphenyl-1-picrylhydrazyl (DPPH) Radical Scavenging, Total Antioxidant Capacity and Total Phenolics Content assays were carried out. One-Dimensional (1D) and two-dimensional NMR and LC-MS analyses were conducted to elucidate structure of the isolated compound.Results and Discussion:The whole plant sample ofE. debileafforded herniarin.Conclusion:The present findings imply thatE. debilecan be a potential source of bioactive components.
Keywords: 7-methoxycoumarin; Bioassay-guided isolation; Equisetum debile; Herniarin